Ferroptosis Inhibition: Mechanisms and Opportunities. (May 2017) - Angeli, Jose Pedro Friedmann; Shah, Ron; Pratt, Derek A.; Conrad, Marcus
Abstract : The past decade has yielded tremendous insights into how cells die. This has come with our understanding that several distinct forms of cell death are encompassed under the umbrella term necrosis. Among these distinct forms of regulated necrotic cell death, ferroptosis has attracted considerable attention owing to its putative involvement in diverse pathophysiological processes. A key feature of the ferroptosis process is the requirement of phospholipid peroxidation, a process that has been linked with several human pathologies. Now with the establishment of a connection between lipid peroxidation and a distinctive cell death pathway, the search for new small molecules able to suppress lipid peroxidation has gained momentum and may yield novel cytoprotective strategies. We review here advances in our understanding of the ferroptotic process and summarize the development of lipid peroxidation inhibitors with the ultimate goal of suppressing ferroptosis-relevant cell death and related pathologies. Trends: Ferroptosis is a recently recognized form of cell death belonging to the group of regulated necrotic cell death modalities characterized by phospholipid oxidation. Ferroptosis is suppressed by one member of the glutathione peroxidase family, namely GPX4. Lipid metabolism determines sensitivity to ferroptosis. Ferroptosis can be inhibited by small molecules at different molecular steps. Inhibition of ferroptosis may provide novel therapeutic opportunities for previously untreatable conditions.